Letter to State of Georgia Executive Department - Colquitt, Alfred (My University, 1897)
Letter from Alfred Colquitt to State of Georgia Executive Department, Atlanta, Georgia. January 9, 1879.
Letter from Alfred Colquitt to State of Georgia Executive Department, Atlanta, Georgia. January 9, 1879.1 handwritten letter on stationary. 1 page.
Keywords: Letters; Records and correspondence; Georgia; Atlanta (Ga.); Colquitt, Alfred Holt, 1829-1894